Restarting Cuba -USA relations: a “new chapter” in USA relations with Latin America ? - Jilola Sh. Ulugova (Ибероамериканские тетради, 2016)
The article focuses the attention on the analysis of the changes that face the Cuban-American relations. On December 17, 2014 two leaders announced their decision to restore diplomatic relations after half a century of hostilities. Since then, they have achieved signiﬁcant progress, but Cuba and USA still have many accounts to pay before the standardization process can be ﬁnished. These outstanding issues are the economic blockade of Cuba and the return of Guantanamo Bay under the jurisdiction of the Cuban authorities. However, it is clear that the rapprochement between the old antagonists has removed the stumbling block that for the long time was hindering the inter-American relations.Where will go Cuba-USA relations? Can we say that “restarting” proclaimed by Obama in 2009 is realy im-plemented? Will the two countries overcome the discrepancies that still exist and prevent the further development of promising dialogue? Or USA domestic politics with its sophisticated decision-making mechanism will hinder this process? These are the questions that aims to address the author in the article.